A formação do professor de canto: Um estudo dos conteúdos de pedagogia vocal no curso de Licenciatura em Artes-Habilitação em Música da Universidade Estadual de Montes Claros - Barbosa, Larissa Márcia Mendes (2023)
The main objective of this research study is to examine how the teaching and learning of vocal pedagogy is carried out in the Music Teacher Training course at the State University of Montes Claros. The specific aims include the need to identify which subjects in the Curriculum address areas related to voice and to know the techniques formulated by the teacher of Vocal Education and Diction. In addition, the study seeks to understand the perceptions that the Vocal Education and Diction teacher has of the pedagogical beliefs underlying the course for training singing teachers and to determine how the students of the singing course in the last year of the course employed vocal pedagogy during their studies. Finally it is essential to understand how students establish a link between these areas with their musical performance and teaching practice and to reflect the perceptions of these students to the vocal pedagogical training that they were given. The literature review included research concerned with the pedagogical aspects of singing teaching techniques and singing teacher training. The theoretical framework was based on the concepts and ideas of Tardif (2002), while the methodology adopted a qualitative approach and consisted of a case study. The data collection involved conducting semi-structured interviews with students in their last year of the singing course and with a teacher of the theoretical and practical aspects of Vocal Education and Diction. The results of this research suggest that the learning process of vocal pedagogy contents by singing students teachers occurs during their performance rehearsals and in educational contexts where they practice their teaching skills. The results also demonstrate that the learning processes of vocal pedagogy reflect the teaching approach being adopted and the importance of the kind of vocal pedagogy selected by the teacher during the training course of the singing teacher.